IMPLEMENTASI MEDIA VISUAL KONKRET DALAM PENGENALAN KONSEP IBADAH PADA ANAK USIA SEKOLAH DASAR - Slamet Riadi; Itsna Rusydiana (LPPM IAD Probolinggo, 2026)
This study aims to describe the implementation of concrete visual media in introducing worship concepts to elementary school students at SDIT Sabilil Mukminin. The research employed a qualitative approach with a descriptive design. Data were collected through in-depth interviews, classroom observations, and documentation involving Islamic Religious Education teachers and the school principal. The data were analyzed using qualitative procedures, including data reduction, data display, and inductive conclusion drawing. The findings reveal that concrete visual media such as sequential images of wudhu and prayer movements, worship procedure posters, and simple teaching aids were applied to support students’ understanding of worship concepts in a more tangible and structured way. The use of these media positively influenced students’ engagement by increasing attention, learning motivation, and accuracy in performing worship practices. School policies that promote active and contextual learning also supported the implementation. However, several challenges were identified, including limited instructional time and differences in students’ ability to interpret visual stimuli. Overall, concrete visual media serve as an effective learning alternative for worship education at the elementary level.